Subcellular targeting and dynamic regulation of PTEN: implications for neuronal cells and neurological disorders - Kreis, Patricia; Leondaritis, George; Lieberam, Ivo; Eickholt, Britta J. (Frontiers in Molecular Neuroscience, 2014)
PTEN is a lipid and protein phosphatase that regulates a diverse range of cellular mechanisms. PTEN is mainly present in the cytosol and transiently associates with the plasma membrane to dephosphorylate PI(3,4,5)P3, thereby antagonizing the PI3-Kinase signaling pathway. Recently, PTEN has been shown to associate also with organelles such as the endoplasmic reticulum, the mitochondria or the nucleus, and to be secreted outside of the cell. In addition, PTEN dynamically localizes to specialized sub-cellular compartments such as the neuronal growth cone or dendritic spines. The diverse localizations of PTEN imply a tight temporal and spatial regulation, orchestrated by mechanisms such as posttranslational modifications, formation of distinct protein-protein interactions or the activation/recruitment of PTEN downstream of external cues. The regulation of PTEN function is thus not only important at the enzymatic activity level, but is also associated to its spatial distribution. In this review we will summarize (i) recent findings that highlight mechanisms controlling PTEN movement and sub-cellular localization, and (ii) current understanding of how PTEN localization is achieved by mechanisms controlling posttranslational modification, by association with binding partners and by PTEN structural or activity requirements. Finally, we will discuss the possible roles of compartmentalized PTEN in developing and mature neurons in health and disease.